PENEGAKAN HUKUM TERHADAP TINDAK PIDANA PERJUDIAN ONLINE DI WILAYAH HUKUM KEPOLISIAN RESOR KOTA PADANG PANJANG - Lovely Fortuna; Elwi Danil; Yoserwan Yoserwan (LPPM Universitas Ekasakti Padang, 2023)
Criminal offenses related to gambling are regulated in Article 303 of the Indonesian Penal Code (KUHP) and Article 303 bis of the KUHP. Additionally, the criminalization of gambling conducted through electronic media is addressed in Article 27 paragraph (2) of Law No. 19 of 2016 on Amendments to Law No. 11 of 2008 on Electronic Information and Transactions. However, the effective implementation of this law has not yet been enforced in the jurisdiction of the Padang Panjang City Police Resort. The research aims to address the following issues: (1) What efforts are being made by the police authorities in enforcing the law against online gambling in the jurisdiction of the Padang Panjang City Police Resort? (2) What are the inhibiting factors or obstacles faced by the police authorities in enforcing the law against online gambling in the jurisdiction of the Padang Panjang City Police Resort? This research adopts an empirical juridical approach and a descriptive method. Primary data collection involves interviews conducted at the Padang Panjang City Police Resort, while secondary data collection entails document analysis. The research findings reveal that law enforcement efforts against online gambling in the jurisdiction of the Padang Panjang City Police Resort can be carried out through preventive measures such as public awareness campaigns and collaborations with relevant parties. Repressive measures include gathering information from the community, investigation and prosecution, site blocking, and providing rehabilitation for offenders. The obstacles faced by the police authorities include weaknesses in the Electronic Information and Transactions Law No. 11 of 2008, lower penalties for online gambling offenses compared to those in Article 303 of the KUHP, difficulties in obtaining evidence through the internet, lengthy case processing, and inadequate understanding and skills of investigators in the field of information technology.